1959
DOI: 10.1021/ja01513a002
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Methyl-Oxygen and the Methyl-Nitric Oxide Reactions by Flash Photolysis1

Abstract: R e la tiv e Energy of th e F la sh (4000-3000 A.) as a F unction of Timej F la sh Energy, 4800 J o u le s. .. . 50 16. A b so rp tio n S p e c tra of Azomethane Before and A fte r th e F l a s h .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1959
1959
1970
1970

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 1 publication
2
27
0
Order By: Relevance
“…and the extrapolation of the ratio of second-order rate constants kz/k, to infinite pressure, yielding the limiting value k,/k, = 0.16 [12]. An independent study of the competition for methyl radicals between reaction (3) and the third-order process : Sleppy and Calvert's technique [13] differs from our own in three respects. First, their photolytic radiation comprised all wavelengths transmitted by quartz, whereas we filtered out all wavelengths shorter that c 300 nm with Pyrex glass.…”
Section: B the Combination Of The Methyl Radical With Nitric Oxide Amentioning
confidence: 95%
“…and the extrapolation of the ratio of second-order rate constants kz/k, to infinite pressure, yielding the limiting value k,/k, = 0.16 [12]. An independent study of the competition for methyl radicals between reaction (3) and the third-order process : Sleppy and Calvert's technique [13] differs from our own in three respects. First, their photolytic radiation comprised all wavelengths transmitted by quartz, whereas we filtered out all wavelengths shorter that c 300 nm with Pyrex glass.…”
Section: B the Combination Of The Methyl Radical With Nitric Oxide Amentioning
confidence: 95%
“…Nitric oxide reacts readily with alkyl radicals remov ing them from the system and breaking the chain reactions in which they are involved (25,27,81) as shown in reaction 30.…”
Section: (24)mentioning
confidence: 99%
“…In the study here reported an accurate rate could be determined after only a few tenths of one per cent conversion of the reactants. The concentrations of the products were determined a t the characteristic absorption regions: peroxyacetic acid, 8 Fig. 1, and recorded during run 2 of Table I).…”
Section: Procedures and Resultsmentioning
confidence: 99%
“…Reaction [4] would not have the three-body restrictioil which has been observed for the reaction of methyl radicals with 0 2 (6,7,8), and it would be considerably faster. \Ve consider the mechanism here proposed to be a reasorlable postulate which is consistei~t with the facts a t hand and is worthy of further testing.…”
Section: Revised Lldechanisnz Of Acetaldehyde Photooxidationmentioning
confidence: 91%